Pengembangan Pendidikan Karakter Melalui Pembelajaran Portofolio di Perguruan Tinggi - Mawara, Ricky (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
Human rights education is a course that seeks to teach about how ideally every human being treats other humans (Sitou Timou Tumou Tou). This study aims to understand the perspectives of students (especially Orang Asli Papua (OAP) students) towards human rights education lectures. The method used is descriptive qualitative, with informants as many as 30 students. The results showed that OAP students felt that human rights education was not in accordance with what they saw and felt in real life. Violence, injustice that exists in the end makes their interest in participating in learning reduced. However, as responsible educators, we must be creative educators who are able to attract their interest in learning for the development of civilization in the land of Papua.